Reading Between the Lines - Purdy, Jessica G., author.
1 online resource (348 pages)
Keywords: This book provides an overview of the establishment and use of parish libraries in early modern England and includes a thematic analysis of surviving marginalia and readers' marks. This book is the first direct and detailed analysis of parish libraries in early modern England and uses a case-study approach to the examination of foundation practices, physical and intellectual accessibility, the nature of the collections, and the ways in which people used these libraries and read their books.